Vergence-Accommodation Conflict: Increased Presbyopia in Virtual Reality - Huang, Ying-Yin; Menozzi, Marino; Lee, Chia-Yen (Klinische Monatsblätter für Augenheilkunde, 2024)
Background Performance and symptoms in completing a visual search task on a PC monitor and using a head-mounted display (HMD) were compared for different viewing conditions and between users of different ages.Patients and Methods Twenty-three young (M = 30 y, SD = 7 y) and 23 older (M = 52 y, SD = 5 y) participants performed a visual search task presented on a PC monitor. The task was repeated using an HMD for a near and a far virtual viewing distance. Reaction times (RT), detection sensitivity (d′), and symptoms were recorded for the three different viewing conditions.Results RT and d’ were not affected by the viewing condition (p > 0.05). In contrast, symptoms significantly depended on the viewing condition but were, in part, not significantly affected by age. It is interesting to note that although not significant, young participants reported more ocular symptoms than older participants in the near vision task carried out using the HMD.Discussion HMD increases visual symptoms. However, HMD could be, in part, a remedy to problems when using visual aids for near work, in particular for presbyopes.
Keywords: virtual reality; near work; vergence-accommodation conflict; vision aids